Counter-reference and reference system organization in the health system context: nurses’ perception - Juliani, Carmen Maria Casquel Monti; Ciampone, Maria Helena Trench (Revista da Escola de Enfermagem da USP, 1999)
This study aimed to understand and to care counter-reference and reference system upon the context of the Health System in Botucatu-SP, Brazil from the nurses who experience this practice. We adopted a qualitative research, situated fenomena model, methodologically derived from phenomenology. In the first part of this study there is a brief presentatiori record about the Health System in Brazil contextualizing as it follows counter-reference and reference system. Results were obtained through ideographic analysis and nomothetic analysis from the testimony of 13 nurses interviewed, bringing 13 themes, reduced into 3 categories: counter-reference and reference system operation, guiding possibilities and local system structural factors. This study showed that this purpose is still an horizont that depend's the isolately professional liability.